2020
DOI: 10.3390/ijms21249620
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BRD4 Reduces Neutrophil Activation and Adhesion to the Vascular Endothelium Following Ischemia Reperfusion Injury

Abstract: Renal ischemia reperfusion injury (IRI) is associated with inflammation, including neutrophil infiltration that exacerbates the initial ischemic insult. The molecular pathways involved are poorly characterized and there is currently no treatment. We performed an in silico analysis demonstrating changes in NFκB-mediated gene expression in early renal IRI. We then evaluated NFκB-blockade with a BRD4 inhibitor on neutrophil adhesion to endothelial cells in vitro, and tested BRD4 inhibition in an in vivo IRI model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 106 publications
2
13
0
Order By: Relevance
“…79 Similarly, Reid et al studied the effects of MS417, a BRD4-specific inhibitor designed to inhibit BRD4 from interacting with RelA, thus inhibiting NFkB-mediated transcription. 24,84 After IRI, mice treated with MS417 had reduced recruitment and activation of neutrophils in the kidney tissue and reduced tubular injury. 24 In another approach, Zhao et al treated rats with total flavonoids which activate silent information regulator factor 2-related enzyme 1 (sirt1), a histone deacetylase that targets RelA at lysine 310 in the nucleus.…”
Section: Targeting Receptors Leading To Nfkb Activationmentioning
confidence: 99%
See 3 more Smart Citations
“…79 Similarly, Reid et al studied the effects of MS417, a BRD4-specific inhibitor designed to inhibit BRD4 from interacting with RelA, thus inhibiting NFkB-mediated transcription. 24,84 After IRI, mice treated with MS417 had reduced recruitment and activation of neutrophils in the kidney tissue and reduced tubular injury. 24 In another approach, Zhao et al treated rats with total flavonoids which activate silent information regulator factor 2-related enzyme 1 (sirt1), a histone deacetylase that targets RelA at lysine 310 in the nucleus.…”
Section: Targeting Receptors Leading To Nfkb Activationmentioning
confidence: 99%
“…However, particular considerations are required in regard to BRD4 inhibitors because these compounds may have broader effects on gene expression beyond the inhibition of NFkB. 24,[87][88][89]…”
Section: Targeting Receptors Leading To Nfkb Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…BRD4 inhibition has been demonstrated to reduce neutrophil recruitment and activation and decrease inflammatory gene expression in primary tubule cells. 19 Zhu et al reported that the elevated IL-1β, TNF-α, and phosphorylated NF-κB levels in Ang II-incubated cardiomyocytes could be reduced by shBRD4. 9 In a mouse model of heart failure, BRD4 inhibition with JQ1 blocks the transactivation of proinflammatory transcription factors.…”
Section: Discussionmentioning
confidence: 99%